The Role and Importance of Leisure Time in the Life of the Young - Radojević, Tatjana S.; Jaredić, Biljana N.; Minić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
In this paper we consider leisure time as a social phenomenon which requires thorough approach in all spheres of life. Leisure time represents one of significant elements of personal development of children and youth, offering the young the abilities to activate their creative powers and satisfy their interests and needs. For that reason, it is essential for them to develop awareness of quality and structured leisure time. Quality of the leisure time depends on the quality of its contents. In case it is insufficiently planned and directed, leisure time can become a source of unacceptable behaviour and addictions. Therefore, it is of great importance to help the young organise and structure their leisure time as well as include them in creating a program of spending leisure time, where the role of psychiatrists and educators is unquestionable. The aim of this work is to draw attention of both scientific and professional public to the importance of structuring the leisure time for young people.